"It ain't hard no more!" Individualizing instruction for struggling readers. Issue 1 (2nd January 2017) - Stover, Katie; Sparrow, Amanda; Siefert, Bobbi
ABSTRACT: Despite sound instructional practices to develop foundational reading skills with young learners, numerous learners continue to lag behind in literacy learning. Many do not view themselves as readers, lack motivation, and become disengaged with learning in general. This article shares a research-based instructional framework developed by one of the authors, Amanda Sparrow, who tutored a struggling reader. An attitudinal survey was included that revealed the tutee's interest in tractors and dump trucks. With this information, the tutee's interests and differentiated instruction to meet his unique learning needs were considered. Consequently, the tutee eagerly engaged in learning and, ultimately, developed his self-efficacy as a reader. The authors posit this instructional approach may inform mainstream teachers who continue to seek ways to improve the literacy success of all learners.